The Role and impact of Indian Judiciary & Media on LGBTQ Rights: A Detailed Study (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
LGBTQ+ rights in India have undergone a significant transformation over the past few decades, with the judiciary and media playing a crucial role in shaping public perception and legal frameworks. This study aims to examine the evolving role of the Indian judiciary and media in advancing LGBTQ+ rights, focusing on landmark judgments, legislative changes, and media representation. The interplay between constitutional guarantees, societal attitudes, and institutional interventions highlights the dynamic nature of LGBTQ+ rights in India.